The city of Ember : the graphic novel - Middaugh, Dallas (Random House, 2012)
In the year 241, twelve-year-old Lina trades jobs on Assignment Day to be a Messenger to run to new places in her decaying but beloved city, perhaps even to glimpse Unknown Regions.